Case Report: Pirfenidone in the Treatment of Post-COVID-19 Pulmonary Fibrosis - Zhou, Xianglin; Yang, Danhui; Kong, Xianglong; Wei, Chengli; LvQiu, Siqi; Wang, Lin; Lin, Yongkang; Yin, Zhilan; Zhou, Zhiguo; Luo, Hong (Frontiers in Medicine, 2022)
Background: Pulmonary fibrosis is one of the sequelae of the COVID-19, which seriously affects the life of survivors. Currently, there are no optimal medical decisions targeting this population. Case Presentation: We report a 66-year-old female patient without underlying diseases admitted to Changsha Public Health Center because of COVID-19. During hospitalization, she developed co-bacterial infection and ARDS, and received broad-spectrum antibacterial therapy, invasive mechanical ventilation and extracorporeal membrane oxygenation. After the acute phase, she developed post-COVID-19 pulmonary fibrosis subsequently treated with pirfenidone. Over 96 weeks after pirfenidone treatment, her mMRC scores improved to 2 from 4 at discharged. Her 6 minutes walking test distance, total lung capacity, and diffusion capacity for carbon monoxide increased to 309 meters from 188 meters, 72.3% of predicted from 31.7%, and 47.9% of predicted from 30.3%, respectively. Chest CT screened on 2 years after illness onset showed regressing fibrosis. The Hospital Anxiety and Depression Scale, Athens Insomnia Scale, and 36-Item Short Form Health Survey questionnaire all got better. Conclusion: Post-COVID-19 pulmonary fibrosis is a tricky sequelae, and our case suggests that pirfenidone may be an effective treatment option.